ECG-Based Unsupervised Clustering in Coronary Artery Disease Associates with Ventricular Arrhythmia - Madrid, Josseline; Ramírez, Julia; Mincholé, Ana (Jornada de Jóvenes Investigadores del I3A, 2023)
Coronary Artery Disease (CAD) is a leading cause of life-threatening ventricular arrhythmias (LTVAs). This study aimed to identify distinct clusters of CAD individuals based on QRS morphology using a 3-nearest neighbors clustering algorithm. Cluster 1, characterized by the lowest QRS amplitudes and widest QRS complexes, was strongly associated with LTVA risk.